Clinical experience combined with therapeutic drug monitoring of lacosamide. (23rd January 2020) - Svendsen, Torleiv; Brodtkorb, Eylert; Baftiu, Arton; Lossius, Morten I.; Nakken, Karl O.; Johannessen, Svein I.; Johannessen Landmark, Cecilie
Abstract : Objective: Lacosamide (LCM) is an antiepileptic drug (AED) with insufficient clinical experience in patients with intellectual disability (ID). They often have more severe epilepsy with comorbidities. The objective was to evaluate the efficacy and tolerability of lacosamide (LCM) in patients with refractory epilepsy with and without ID in a real‐life setting, taking drug monitoring (TDM) data into account therapeutic. Methods: Retrospectively, we identified 344 patients using LCM from the TDM service covering the majority of the country, at the National Center for Epilepsy in Norway (2013‐2018). Clinical and TDM data were available for 132 patients. Results: Forty‐four of the 132 patients (33%) had ID. The retention rate was significantly higher in the ID vs the non‐ID group after 1 year (84% vs 68%, P  < .05). By combining clinical and TDM data, we demonstrated that 37/38 responding patients had serum concentrations above the lower limit of the reference range (>10 µmol/L), and 16/17 with lower concentrations were non‐responders. Mean serum concentration/dose ratios were similar in both groups, 0.06 and 0.07 µmol/L/mg. There were no significant differences regarding efficacy and tolerability. The risk of LCM withdrawal was significantly higher when LCM was added to sodium channel blockers, even if the latter was discontinued. Significance: Lacosamide was generally well tolerated in patients with drug‐resistant epilepsy, where one third had ID, and in these patients the retention rate was higher. The combination of clinical and TDM data could possibly facilitate LCM therapy in these vulnerable patients.